Prevalence and antibiotic susceptibility patterns of pseudomonas aeruginosa in urinary tract infections in a Tertiary care hospital, Central Kerala: A retrospective study over 4 years - Dr. ReghaI R (Tropical Journal of Pathology and Microbiology, 2018)
Background and Objective: Pseudomons aeruginosa (P.aeruginosa) is an important uropathogenthat has shown varied antibiotic susceptibility patterns. This study aims to findout the changing trends in th eprevalence and antibiotic susceptibility patterns ofurinary isolates of P.aeruginosa over four consecutive years.Methodology: A retrospective, record based study was conducted on all culture and sensitivity (C/S) reports ofurine samples obtained in the microbiology lab in a tertiary care centre, Central Kerala (January 2014 -December 2017). The C/S reports which were positive for significant growth of P.aeruginosa were analyzed to findout its prevalence and antibiotic susceptibility patterns. Descriptive statistics was used for data analysis and the results were expressed in percentages.Result: Out of total 6622 urine samples received (14%) showed significant bacteriuria. P.aeruginosa was the third most common uropathogen isolated with an isolation rate of 3.5%. The antibiotic resistance observed were Gentamicin (53.1%), Amikacin (28%), Cefipime (28%), Ceftazidime(34.4%), Ciprofloxacin (43.7%), Norfloxacin (40.6%), Ofloxacin (40.6%), Piperacillin (37.5%), Piperacilli-Tazobactam (25%) and Imipenem (28%). The isolation rates of P.aeruginosa were 3.9%, 2.6%, 4.5 % and 2.9% in 2014, 2015, 2016 and 2017 respectively and overthe years it maintained its third position.The year wise analysis of antibiotic resistance showed fluctuating pattern except Amikacin, Cefipime and Fluoroquinoles which displayed a decreasingtrend. The reserve drugs like Piperacillin –tazobactam and Imipenem showed alarming drug resistance, although a hopeful reduction in the resistance was noted in 2017.Conclusion: P.aeruginosa remains as a common uropathogen. Drug resistant strains are markedly high in our area. Antibiotic resistance of P.aeruginosado not show a consistent trend over years and vary from region to region. Soeach institution should have an antibiotic policy based on the local antibiogram which is to be renewed regularly. Instead of opting for higher antibioticseach time, strict implementation of restrictive and rotational antibiotic policies and adherence to the concept of ‘Reserve drugs” should be followed. This is the only modality to inhibit the emergence of resistance strains of all uropathogens especially opportunistic pathogens like P.aeruginosa.